2014
DOI: 10.1186/1752-1947-8-416
|View full text |Cite
|
Sign up to set email alerts
|

Five years of local control of subscapularis aggressive fibromatosis managed by surgery and imatinib: a case report

Abstract: IntroductionImatinib, a tyrosine kinase inhibitor, is a major therapeutic option for the management of unresectable aggressive fibromatosis. Unfortunately, for most patients of low or very low average income countries, surgery often is the first treatment option. This is related to unavailability of chemotherapy or targeted therapy, and to a lack of financial resources or surgeons’ lack of knowledge of other therapeutic options.Case presentationIn 2010, a 26-year-old Moroccan man was referred to our oncology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…18,129,130,141,[145][146][147]168,169 Tyrosine kinase inhibitors also have activity in some DTF cases, and meaningful responses have been described. 64,155,156,[169][170][171][172][173][174] In at least 1 case the tumor was responsive to sunitinib but not imatinib at the usual doses, 169 suggesting that in some cases efficacy may be due to effects on targets other than KIT (kit proto-oncogene receptor tyrosine kinase). (Table).…”
Section: Evidence For Clinical Treatments Of Dtfmentioning
confidence: 99%
“…18,129,130,141,[145][146][147]168,169 Tyrosine kinase inhibitors also have activity in some DTF cases, and meaningful responses have been described. 64,155,156,[169][170][171][172][173][174] In at least 1 case the tumor was responsive to sunitinib but not imatinib at the usual doses, 169 suggesting that in some cases efficacy may be due to effects on targets other than KIT (kit proto-oncogene receptor tyrosine kinase). (Table).…”
Section: Evidence For Clinical Treatments Of Dtfmentioning
confidence: 99%
“…Imatinib was the primary drug administered for DF. Additionally, case reports indicated that imatinib exhibited no discernible toxic effects and notably alleviated patient discomfort ( 28 ). In cases of imatinib resistance, sunitinib serves as a viable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive bromatosis has no signs of malignancy in cytological morphology, no lymphatic and blood tract metastasis, but it is invasive, recurring, and locally destructive, which is different from benign and malignant tumors [1][2][3][4] . WHO (1994) de nes it as differentiated broblast tumors, whose biological characteristics are between benign broblast tumors and brosarcomas, and are recognized by more and more scholars [5][6][7][8] . Primary invasive bromatosis of the stomach is rare.…”
Section: Introductionmentioning
confidence: 99%